2021
DOI: 10.1027/1015-5759/a000587
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visual Displays in Attenuating Discrepancies Between Self-Reported and Physiological Indexes of Stress

Abstract: Abstract. This study examined whether the relationship between subjective and physiological outcomes of stress, and the responsivity to stressors, are affected by whether participants can see a visual display of their physiological output. Participants were randomly assigned to have a visible view of their physiological output readings, or to a condition in which physiological output readings were out of view. Participants individually completed a 30-min laboratory study including the modified Trier Social Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…They were therefore aware of how their blood pressure and heart rate changed over the course of the first study visit prior to their second visit. Awareness of physiological responses to a stressor may increase physiological reactivity to the task (e.g., Liu et al, 2020), potentially contributing to an additional unmodeled source of variability in the test–retest calculations.…”
Section: Discussionmentioning
confidence: 99%
“…They were therefore aware of how their blood pressure and heart rate changed over the course of the first study visit prior to their second visit. Awareness of physiological responses to a stressor may increase physiological reactivity to the task (e.g., Liu et al, 2020), potentially contributing to an additional unmodeled source of variability in the test–retest calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Finding only few relationships between subjective and physiological indicators is perhaps not a surprise, as, for example, Liu et al. (2021) concluded on the basis of their study that self‐reported stress and physiological indexes of arousal are relatively distinct components of the individual stress experience (see also Brown et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This latter relationship may relate to the fact that they both were measured at the same time in the afternoon, giving support to the view that stress can temporarily increase blood pressure. Finding only few relationships between subjective and physiological indicators is perhaps not a surprise, as, for example, Liu et al (2021) concluded on the basis of their study that self-reported stress and physiological indexes of arousal are relatively distinct components of the individual stress experience (see also Brown et al, 2020).…”
Section: Daily Sleep Stress and Vigour As An Underlying Mechanismmentioning
confidence: 99%
“…A visual analogue scale is a fast and efficient way to assess the subjective stress level ( Ali et al., 2020 ; Fujiwara & Okamura, 2018 ; J. J. Liu et al., 2020 ; Nakamura et al., 2020) .…”
Section: Methodsmentioning
confidence: 99%